Safely reopening and operating a primary healthcare facility after closure due to SARS-CoV-2 infection in a healthcare worker – Nairobi, Kenya, 2020 - Ndegwa, Linus K.; Kimani, Daniel; Njeru, Mercy; Chen, Tai-Ho; Macharia, Catherine; Ouma, Annalice; Mboya, Frankline O.; Oliech, Julius; Kwambai, Titus K.; Liban, Ahmed; et al. (International Journal of Infection Control, 2024)
The first COVID-19 case in a healthcare worker in Kenya was reported on March 30, 2020, in Nairobi, leading to a 41-day closure of the health facility where he had worked. We assessed infection prevention and control (IPC) activities and implemented recommendations to re-open and operate the facility. We conducted a risk assessment of the facility in April 2020 using a modified World Health Organization, six-element IPC facility risk assessment tool. IPC recommendations were made, and a follow-up assessment of their implementation was conducted in July 2020. Breaches in IPC measures included poor ventilation in most service delivery areas; lack of physical distancing between patients; inadequate COVID-19 information, education, and communication materials; lack of standard operating procedures on cleaning and disinfecting high-touch areas; insufficient IPC training; inadequate hand hygiene facilities; insufficient personal protective equipment supplies; and an inactive IPC committee. Strengthening IPC measures is critical to prevent healthcare facility closures.